2020
DOI: 10.3389/fpls.2020.580833
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Multiple Components Contributing to Fusarium Head Blight Resistance of FL62R1, a Canadian Bread Wheat Developed Using Systemic Breeding

Abstract: Fusarium head blight (FHB) is a devastating fungal disease of small-grain cereals that results in severe yield and quality losses. FHB resistance is controlled by resistance components including incidence, field severity, visual rating index, Fusarium damaged kernels (FDKs), and the accumulation of the mycotoxin deoxynivalenol (DON). Resistance conferred by each of these components is partial and must be combined to achieve resistance sufficient to protect wheat from yield losses. In this study, two biparental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 91 publications
2
27
0
Order By: Relevance
“…Genetic resistance to FHB is quantitative and is the result of several loci that contribute to molecular and physiological differences in the wheat plant. To date, more than 65 quantitative trait loci (QTL) have been identified that contribute to FHB resistance in wheat ( Venske et al, 2019 ), including North American breeding material ( McCartney et al, 2016 ) such as FL62R1 ( Comeau et al, 2008 ; Zhang et al, 2018 , 2020 ), as well as cultivars, such as Alsen, Glenn, Carberry, and AAC Tenacious ( Bokore et al, 2017 ; Dhariwal et al, 2020 ). Pyramiding FHB resistance QTL increases disease resistance ( Venske et al, 2019 ), but unfortunately, many FHB resistance QTL are also associated with poor agronomics and quality, making their transfer into elite varieties a challenge ( Haile et al, 2019 ; Venske et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic resistance to FHB is quantitative and is the result of several loci that contribute to molecular and physiological differences in the wheat plant. To date, more than 65 quantitative trait loci (QTL) have been identified that contribute to FHB resistance in wheat ( Venske et al, 2019 ), including North American breeding material ( McCartney et al, 2016 ) such as FL62R1 ( Comeau et al, 2008 ; Zhang et al, 2018 , 2020 ), as well as cultivars, such as Alsen, Glenn, Carberry, and AAC Tenacious ( Bokore et al, 2017 ; Dhariwal et al, 2020 ). Pyramiding FHB resistance QTL increases disease resistance ( Venske et al, 2019 ), but unfortunately, many FHB resistance QTL are also associated with poor agronomics and quality, making their transfer into elite varieties a challenge ( Haile et al, 2019 ; Venske et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A multi-parental spring wheat ( Triticum aestivum L.) population (double haploid population) derived from the cross of FL62R1 (as common parental line) with Stettler, Muchmore, and Emerson was developed as described previously [ 17 ]. FL62R1 is an Eastern Canadian spring wheat line with comparable resistance to Sumai 3, developed by Comeau et al [ 59 ] with a systemic breeding approach.…”
Section: Methodsmentioning
confidence: 99%
“…The multi-parent population was evaluated for FHB resistance in disease nurseries at Carman, Manitoba (MB) and Ottawa, Ontario (ON) in 2015 and 2016 with three biological replications and a random complete block design (RCBD) in single meter rows. Disease trait evaluation and phenotyping were described in detail by Zhang et al [ 17 ]. The evaluated FHB and related traits included INC, SEV, FDK, and DON levels.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations